EFFECT OF IRRADIATION IN HONEY INOCULATED WITH Bacillus sporothermodurans - Valter Arthur (Brazilian Journal of Radiation Sciences, 2021)
Honey is a natural viscous product widely used for nutritional and medicinal purposes. Although it’s a food that  presents a high degree of resistance  against  the  growth  of microorganisms  is not  a sterile medium. Spore-forming bacteria, such as Clostridium botulinum, are present in honey and it’s the only recorded  source  of  food  carrier  of  the  agent  that  causes  childhood  botulism.  The  steps  of  honey processing do not include the heat treatment for its commercial sterility, due to the application of heat increase the presence of hydroxymethylfurfural.  Food  irradiation  is a  method  of preservation  that can  be  applied    in    the  processing    of  honey  by  not  physically  altering  the  appearance,  shape  or temperature of the product. The objective of this work was to evaluate the effect of gamma irradiation on  honey  inoculated  with  Bacillus  sporothermodurans  spores.  The  inoculation  of  106   CFU.mL-1   of lyophilized culture of this bacterium in the honey samples was carried out and the irradiation of the samples at 5, 10 and 15 kGy doses was carried out. After irradiation, the samples were incubated at 30o C for 72 h in Brain Heart Infusion (BHI) agar. The count present reduction of one logarithmic cycle in the number of colonies in the 5 kGy irradiated honeys. In the samples irradiated with doses of 10 and 15  kGy  there  was  no  microbial  growth  and  spore  germination.  It’s  concluded  that  irradiation constitutes  an  excellent  conservation  method,  which  can  be  used  to  guarantee  the  microbiological quality of the honey.